Selection Criteria for Radiographic Images in Dentistry: A Comprehensive Review of Updated Standards - Barba Ramírez, Lucía; Ruiz-Imbert, Ana Cecilia; Cascante-Sequeira, Deivi (Odovtos - International Journal of Dental Sciences, 2025)
Radiographic images play a crucial role in dentistry for diagnosis, treatment planning, and follow-up. However, due to the potential risks associated with ionizing radiation, such studies should only be conducted following a comprehensive patient history and clinical evaluation that justify their necessity. In the dentistry field, various radiographic techniques are available to acquire both intraoral and extraoral images, as well as two-dimensional and three-dimensional images. The selection of an imaging technique should be guided by its diagnostic efficacy, that is, how effectively it meets the patient's needs. Each imaging method possesses unique advantages and limitations, influenced by technical factors, and must be tailored to the specific diagnostic requirements of individual cases. This review aims to provide an evidence-based update on the criteria for choosing imaging techniques across the various areas of dental specialization.